2012
DOI: 10.1002/pbc.24241
|View full text |Cite
|
Sign up to set email alerts
|

Improved care of rhabdomyosarcoma in Jordan using less intensive therapy

Abstract: BackgroundThe care of rhabdomyosarcoma (RMS) is complex due to its multimodal nature. By following standard protocols with acceptable toxicity and building local expertise, better outcome should be achievable.ProcedureA retrospective study was conducted of records of patients (n = 45; 31 males; median age 26 months) with RMS treated at King Hussein Cancer Center in Jordan from January 2004 to December 2008. Patient demographics, tumor characteristics, risk stratification, treatment plan, and outcomes were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
(36 reference statements)
1
3
0
1
Order By: Relevance
“…This study showed that the survival rates achieved in high‐income countries with treatments for children with RMS were unlikely to be reproduced in Central America. The AHOPCA results are similar to those reported in other resource‐limited settings 9–13,22–25 . However, this finding is at odds with the results obtained with treatments for other pediatric malignancies, such as retinoblastoma 26 and Hodgkin 27 or non‐Hodgkin lymphomas, 28 for which the survival rates achieved with AHOPCA protocols were not so different from those usually reported in developed countries.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…This study showed that the survival rates achieved in high‐income countries with treatments for children with RMS were unlikely to be reproduced in Central America. The AHOPCA results are similar to those reported in other resource‐limited settings 9–13,22–25 . However, this finding is at odds with the results obtained with treatments for other pediatric malignancies, such as retinoblastoma 26 and Hodgkin 27 or non‐Hodgkin lymphomas, 28 for which the survival rates achieved with AHOPCA protocols were not so different from those usually reported in developed countries.…”
Section: Discussionsupporting
confidence: 77%
“…The AHOPCA results are similar to those reported in other resource-limited settings. [9][10][11][12][13][22][23][24][25] However, this finding is at odds with the results obtained with treatments for other pediatric malignancies, such as retinoblastoma 26 and Hodgkin 27 or non-Hodgkin lymphomas, 28 for which the survival rates achieved the years to reduce the rate of patients abandoning their treatments, including programs for social workers covering advocacy and community education, and financial support for families. 29,30 Our analysis suggested that a main cause of the survival gap between Central America and developed countries may concern the quality of local control (local progression/relapse was the main cause of treatment failure).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1). Несмотря на эти ограничения, успешные результаты были достигнуты в лечении солидных новообразований, таких как ретинобластома [35], саркома [70,71] 20 П р о г р е с с в д е т с к о й г е м а т о л о г и и -о н к о л о г и и в X X I в е к е В то время как глобальные инициативы в области здравоохранения для терапии онкологических заболеваний у детей становятся все более распространенными, параллельно проводится работа в области детской гематологии. Аналогично ЗН, ежегодно примерно 80 % новорожденных детей в странах с низким и средним уровнем доходов страдают гемоглобинопатиями.…”
Section: разработка адаптированного леченияunclassified